The Effect of Learning Styles on Academic Achievement of EFL Students in Islamic Institution - Palmatiwi, Dyah Hanum; Putri, Fara Suseno; Rianti, Nur Peniy; Khairunnisa, Rahmahdalena Putri; Rani, Rani; Rahmawati, Siti; Syahid, Abdul (Journal of English Language and Education, 2026)
A substantial body of research suggests that learning styles contribute to learners’ academic performance; however, evidence regarding their influence in tertiary-level EFL contexts remains inconsistent. While many studies report positive correlations between learning styles and language achievement, recent findings indicate that learning style differences do not always lead to significant performance variations. This inconsistency highlights the need for further investigation, particularly in Islamic higher education settings where empirical studies are still limited. Therefore, this study aims to examine whether learning styles—visual, auditory, and kinesthetic—significantly affect the academic achievement of EFL students. Employing a quantitative ex post facto design, data were collected from 30 students using a learning style questionnaire adapted from DePorter et al. (2007) measured through a five-point Likert scale, along with official final exam scores from English skill courses. The data were analyzed using One-Way ANOVA, Tukey HSD, and a Kruskal–Wallis test. The results revealed no significant differences in academic achievement among the three learning style groups, F(2, 27) = 0.334, p = 0.719, a finding reinforced by the non-parametric test (p = 0.864). Although kinesthetic learners showed slightly higher mean scores, the differences were not statistically meaningful. These findings suggest that learning styles do not significantly influence EFL students’ academic achievement in Islamic higher education. The study underscores the importance of adopting multimodal and flexible instructional approaches rather than relying solely on learning style-based teaching.